Alexander Dubček unknown (1921-1992) : the life of a political icon - Baer, Josette (Stuttgart ; La Vergne : Ibidem Press, 2018)
Alexander Dubcek is well-known, so one might think; nothing new can be written about him. Is this true' Dubcek is the symbol of the Czechoslovak attempt to reform communism that gained worldwide admiration in 1968. The invasion of Warsaw Pact troops in the night of August 21, 1968 set a brutal end to the Prague Spring. Josette Baer's new biography focuses on Dubcek's early years, his childhood in Soviet Kirghizia, his participation in the Slovak National Uprising in 1944 against Nazi Germany and the Slovak clerical-fascist government, and his career in the Slovak Communist Party in the late 1950s and early 1960s. It offers new insights into the political thought of the father of 'Socialism with a Human Face, ' based on archive material available to the Western reader for the first time. Who was Alexander Dubcek'a naIve apparatchik, an independent thinker, a courageous liberator, or a political dreamer'
Introduction -- Childhood, early years and education (1921-1939) -- Dear Sasha : a career in the Communist Party (1939-1968) -- Oblivion? : Dubček's dissent and return to politics (1969-1992) -- Conclusion -- Oral history interview with Pavol Dubček, MD -- Oral history interview with Professor Ivan Laluha -- Oral history interview with Mr. Miloslav Liška.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Dubček, Alexander, -- 1921-1992.; Dubček, Alexander, -- 1921-1992; Politicians -- Slovakia -- Biography; Politiciens -- Slovaquie -- Biographies; HISTORY -- Europe -- Germany; Politicians; Slovakia; Biographies